Individuale e globale. L’irripetibile unicità di Diego - Russo, Pippo (Eracle. Journal of Sport and Social Sciences, 2022)
On the day of his death, Diego Armando Maradona was definitively elevated to the status of global leader with a universal message. The media mobilization that was triggered immediately, in addition to breaking the thematic monopoly of covid in the global communication agenda, has decreed a status that had never been assigned to a sports personality. And the unanimity registered by the emotional reaction of global public opinion has also healed the divisive character that instead the figure of Diego Armando Maradona had been in life. From this starting point, the essay intends to propose a variation on Maradona as a global and transversal cultural phenomenon, capable of affirming itself as such by enhancing the propensity for an individualism full of a sense of challenge and never inclined to mediation. The essay also takes into account a particular dimension of the figure of Maradona: that of being a global and Italian phenomenon at the same time. A global phenomenon, because it belongs to the whole of humanity and proved it for the umpteenth time on the day of his death, when the media around the world interrupted the information monopoly of the pandemic for a couple of days to give space to a great media ceremony of homage to the genius. An Italian phenomenon, because it was during the years spent in Italy that Maradona became the greatest ever and achieved the most significant successes.